Cryptocurrencies in public and private law - Fox, David; Green, Sarah; Carr, Daniel J. (Oxford University Press, 2019)
This book examines how cryptocurrencies based on blockchain technologies fit into existing general law categories of public and private law. The book takes the common law systems of the United Kingdom as the centre of its study but extends beyond the UK to show how cryptocurrencies would be accommodated in some Western European and East Asian legal systems outside the common law tradition.0By investigating traditional conceptions of money in public law and private law the work examines the difficulties of fitting cryptocurrencies within those approaches and models. Fundamental questions regarding issues of ownership, transfer, conflict of laws, and taxation are addressed with a view to equipping the reader with the tools to answer common transactional questions about cryptocurrencies. The international contributor team uses the common law systems of the United Kingdom as a basis for the analysis, but also looks comparatively to other systems across the wider common law and civil law world to provide detailed examination of the legal problems encountered.